Preparation of Silicone-Modified Acrylic Ester Emulsion Adhesive with Core-Shell Structure - Sui, Zhihui; Pang, Weiwei; Song, Jia; Zhang, Lei; Zhao, Xin (Asian Journal of Chemistry, 2014)
Silicone-modified acrylate emulsion adhesives with core-shell structure was synthesized by semi-continuous seed emulsion polymerization with vinyl silane three oxygen radicals (A-171), methyl methacrylate, butyl acrylate and acrylic acid as raw material and was used for fabric pigment printing. The structure of the adhesive was characterized and analyzed by FT-IR spectrum, XPS and TEM. The results indicated that the organic silicon modified acrylate emulsion adhesive was synthesized in the optimum condition that the dosage of initiator, emulsifier and A-171 was 1.3, 3 and 4 %, respectively and reaction temperature was 80 °C for 1 h. At this point, the monomer conversion rate was as high as 95.01 %, the gel rate was 0.71 % and the water absorption was only 35.60 % of the unmodified latex film. After adhesive was used for pigment printing, the fabric dry and wet friction fastness reached level 4-5 and 3-4, soaping staining and fading grade reached 4-5 and 4, respectively and bending rigidity was 2.13; Compared with the commercial adhesives, good comprehensive performance such as high colour fastness and soft hand feel could be obtained and free of formaldehyde was released.